Phraseodidaktik an der Schnittstelle zur Grammatik- und Wortschatzarbeit im DaF/DaZ- und im sprachsensiblen (Fach-) Unterricht am Beispiel von festen nehmen-Konstruktionen: Annäherung an eine pragmasemantische Konstruktionsdidaktik - Ránics, László (Linguistik Online, 2021)
In this paper, I investigate if phraseodidactic approaches can be transferred to grammar and vocabulary training in foreign language lessons to the same extent. Taking a usage-based approaches to foreign and second language didactics, it is shown that phraseologisms can be subjected to structural semantic analyses in foreign language lessons for learners to develop (i) phraseological language awareness and (ii) adequate phraseological language skills. On the basis of the analyses and the recommendations for basic and advanced phraseological vocabulary, a new approach of pragmatic-semantic construction didactics is introduced.